The landscape identity of the Longjing temple and its relation with the tea cultivation - Mezcua López, Antonio José (Estudios Complutenses de Asia Oriental, 2025)
In this article the relationship between Longjing temple and tea through its historical evolution is examined using the methodologies of landscape studies. It demonstrates how specific geographical conditions give rise to a transformation of the landscape from a material point of view and in the different narratives that are built around it. In this sense, we will demonstrate that the fame of Longjing tea raise from the Buddhist landscape identity of the site and later on will parallel the resurgence of West Lake as famous landscape and tourist destination in Ming and Qing periods.
Keywords: Longjing; tea; landscape; West Lake; Chinese garden